PENGARUH LATIHAN SHUTTLE RUN TERHADAP PENINGKATAN KELINCAHAN GERAK SHADOW 6 TITIK PADA ATLET PUTRA BULUTANGKIS PB. CHEVRON PEKANBARU - Yelli Apriyanti; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this research was to see whether there is a significant effect of shuttle run training (X) on the increase in agility (Y) in badminton male athletes PB. Chevron Pekanbaru. This research was conducted at the Enau Complex, Gelora PB.Chevron, from November 2019 to January 2021, while the training process itself was given after the new normal from June 22 to July 31 2020 for 18 meetings by following the standard covid-health protocol. 19. From the results of successful research, the shuttle training method is quite effective in increasing the agility of the 6-point shadow motion using exercise doses for 16 times face to face. The shuttle run exercise is a component of agility training, so an increase in the agility of the 6-point shadow motion can occur in this research. This is evidenced by the increase in shuttle run data with a mean of 2.14 points / 30 seconds. So it can be summarized that there is a significant effect of shuttle run training (X) on increasing agility (Y) in badminton male athletes PB. Chevron Pekanbaru.Key Words: Effect, Shuttle Run Exercise, Motion Shadow 6 points